Peningkatan Daya Jual Produk Anyaman Bambu Desa Kanyoran Kabupaten Kediri Berbasis WEB - Sjamsul Hidajat; Zudha Pratama; Dibyo Adi Wibowo; David Febrian Natanael; Muhammad Burhanudin; Silfi Andriana Puspa; Shinta Rachma Yulianti (P3M Politeknik Negeri Malang, 2025)
This research aims to evaluate the web system training conducted in Kanyoran Village, Kediri Regency, focusing on the development of applications that benefit the community. The issue faced by the villagers is the lack of understanding and skills in utilizing digital technology for marketing their craft products, particularly bamboo weaving. In response to this challenge, the research employs a step-by-step training method, beginning with an introduction to the material and extending to the use of hosting services. Over the course of two days, participants were equipped with practical skills through interactive teaching designed to enhance their knowledge and confidence in using digital applications. The evaluation results indicate that the majority of participants found the training material easy to understand, the developed application useful, and the hosting training sufficiently clear. The questionnaires filled out by participants revealed that 70% of respondents felt motivated to use the application for further marketing. Thus, the training successfully achieved its goal of improving the community's understanding and skills in leveraging digital technology. Recommendations for future activities include extending the training duration and providing more hands-on practice sessions to enhance participants' confidence in using the application, as well as incorporating advanced modules that cover deeper digital marketing strategies